Violence, life aspirations and displacement trajectories in civil war - Lea Müller-Funk (International Migration, 2023)
Drawing on qualitative data from the civil wars in Syria and Libya since 2011, this paper seeks to build a better understanding of immobility and of displacement trajectories within conflict countries and towards neighbouring countries. The paper shows that different types of violent experiences—personal threats, generalized violence, an increasing hopelessness relating to the absence of violence in the future—trigger different exit movements across internal and external borders. Second, the analysis demonstrates that migration decisions in civil war contexts are complex processes with people balancing between strategies of how to avoid violence with strategies of how to realize broader life aspirations related to family, love, work and political change. Life aspirations often play a more important role once people move out of a situation of immediate danger and in later phases of trajectories and influence (im)mobility patterns in three different directions: stay, move (on) or return. Life aspirations, especially related to political change, outweigh perceptions of violence in some cases. Financial vulnerability can force people to stay in or return to violent contexts.
Keywords: 300